Evaluation of the use of e-learning in the implementation of the "Stake's countenance" model in the era of the Covid 19 pandemic - Retnowati, Trie Hartiti; Kuswarsantyo, Kuswarsantyo; Prihadi, Bambang; Wulandari, Aldia; Alya, Winny Chrisan; Rafika, Tria (Imaji: Jurnal Seni dan Pendidikan Seni, 2023)
The learning process in the Master of Arts Education Study Program during the Covid-19 pandemic experienced problems not being able to hold meetings offline. The purpose of the study was to evaluate the use of e-learning with a countenance stake model. This research uses a qualitative evaluation method with a countenance evaluation model by Stake. Matters evaluated include (1) Antecedent (context, input); (2) Transactions (processes) and (3) Outcomes (results) of curriculum implementation. The results showed that learning in the Master of Arts Education Study Program during the Covid-19 pandemic went smoothly. A total of 21.57% of the smooth learning process has the category of mostly smooth meetings. The suitability of student learning outcomes with CPL was 88.46%. CPL Based on the results of the questionnaire, data was obtained that the achievement of appropriate student learning outcomes (80-100%) was 83.33%. These results illustrate that student learning outcomes are fulfilling the aspect of achievement. Keywords: Art learning, evaluation, countenance stake Evaluasi pemanfaatan e-learning dalam pelaksanaan pembelajaran dengan model “countenance stake” di era pandemi Covid 19AbstrakProses pembelajaran di Program Studi Magister Pendidikan Seni masa pandemi covid-19 mengalami kendala tidak bisa melakukan pertemuan secara luring. Tujuan penelitian untuk mengevaluasi penggunaan e-learning dengan model countenance stake. Penelitian ini menggunakan metode evaluasi kualitatif dengan model countenance evaluation oleh Stake. Hal-hal yang di evaluasi meliputi (1) Antecedent (konteks, input); (2) Transaction (proses) dan (3) Outcomes (hasil) pelaksanaan kurikulum. Hasil penelitian menunjukkan bahwa pembelajaran di Program Studi Magister Pendidikan Seni masa pandemi covid-19 berjalan lancar. Sejumlah 21,57% kelancaran proses pembelajaran memiliki kategori sebagian besar pertemuan lancar. Kesesuaian hasil belajar mahasiswa dengan CPL sebesar 88,46%. CPL Berdasarkan hasil angket diperoleh data bahwa ketercapaian hasil belajar mahasiswa yang sesuai (80-100%) sejumlah 83,33%. Hasil tersebut menggambarkan hasil belajar mahasiswa terlah memenuhi aspek ketercapaian. Kata Kunci: Pembelajaran Seni, evaluasi, countenance stake